Oral Hygiene Education on the Dental and Oral Hygiene Status of Inpatients at Ananda Hospital, Bekasi - Pratiwi, Pegi (Journal Center of Excellent : Health Assistive Technology, 2025)
Background: Indonesian people often experience dental and oral health problems with a prevalence rate of 57.6%. With a caries prevalence of 88.8% and periodontal tissue (gingivitis) reaching 74.1%. In West Java province, dental and oral health problems reach 58.0%. Inpatients have poor dental and oral hygiene status. Objective: to analyze the dental and oral hygiene of inpatients before and after being given oral hygiene education at Ananda Bekasi Hospital in 2024. Method: The research design used was a quasi-experimental study with one group pre-test and post-test before and after oral hygiene education with flipcharts and toothbrush demonstrations were given to patients at Ananda Bekasi Hospital. Results: The results of education for 3 days on 32 inpatients at Ananda Hospital Bekasi showed that before education, patients with good criteria were 3 (10%), patients with moderate criteria were 19 (59%) and poor criteria were 10 patients (31%). After education, patients with good criteria were 8 patients (25%), moderate criteria were 21 patients (65%) and poor criteria were 3 patients (10%). The average difference in oral hygiene status (OHI-S) before and after education was 0.83 with p = 0.04. Conclusion: it can be concluded that oral hygiene education is effective in improving the oral hygiene status of inpatients at Ananda Hospital Bekasi.